Social representations of cancer in patients from Medellín, Colombia: a qualitative study - Higuita-Gutiérrez, Luis Felipe; Estrada-Mesa, Diego Alejandro; Cardona-Arias, Jaiberth Antonio (Frontiers in Sociology, 2023)
Background: Cancer is a life-threatening disease having different explanatory theories addressing its etiology and treatment. It is usually associated with pain and suffering. Recently, new technologies, knowledge, and therapies have developed, which may have transformed the classic social representations of the disease. This study aimed to understand the social representations (SRs) of in patients from Medellín, Colombia.Methods: This study is a grounded theory in 16 patients with cancer. The information was collected between June 2020 and May 2021. The information was analyzed following the open, axial, and selective coding stages.Results: SRs of cancer at the time of diagnosis evoke words with negative connotations. However, cancer is redefined as a positive event in life as the clinical course of the disease progresses and as patients interact with health professionals and respond to treatment. The resignification of the disease depends on the etiological aspects with which patients link it, and these aspects can be genetic, socioanthropological, psychosocial, and psychogenic. In line with the SRs of etiology, patients seek out treatments complementary to the biomedical ones; these treatments can be socio-anthropological and psychogenic.negative representations around cancer persist, which suggests that this way of understanding the disease is embedded in the collective memory. The causal representation is strongly connected to the mechanisms of action and the disposition of the patients in the face of their diagnosis. In this sense, two categories stand out: one that expresses that cancer is the consequence of a body subjected to excessive productivity, and another that subsumes a psychogenic predisposition derived from an environment where the ideology of happiness appears to be a social norm. This double saturation in which an individual is immersed ends up constituting new burdens that are not visible to caregivers and healthcare personnel.